2016
DOI: 10.15376/biores.11.4.10756-10782
|View full text |Cite
|
Sign up to set email alerts
|

Sugar Palm Fibre and its Composites: A Review of Recent Developments

Abstract: The use of natural fibres as reinforcement in composite materials has increased over the years due to the rapid demand for renewable, costeffective, and eco-friendly materials in many applications. The most common and adopted natural fibres used as reinforcements are flax, kenaf, hemp, jute, coir, sisal, and abaca. However, sugar palm fibre (SPF) as one of the natural fibres is gaining acceptance as a reinforcement in composites, though it has been known for decades in the rural communities for its multipurpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 74 publications
0
23
0
Order By: Relevance
“…This is ascribed to the effect of eco‐friendly treatment which, provides an efficient interlocking of fibers with the matrix after elimination of hemicellulose and waxy substances from the sisal fibers . Exclusion of hemicelluloses and lignin after ecofriendly treatment was reported in previous studies . Composite SC (T2) shows the lowest water uptake credited to a combined effect of eco‐friendly treatment and coating which provides strong interfacial bonding as the treatment eliminates the hemicellulose and lignin, and coating makes the fibers more hydrophobic and acts as a protective layer which strongly opposes to the water absorption…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…This is ascribed to the effect of eco‐friendly treatment which, provides an efficient interlocking of fibers with the matrix after elimination of hemicellulose and waxy substances from the sisal fibers . Exclusion of hemicelluloses and lignin after ecofriendly treatment was reported in previous studies . Composite SC (T2) shows the lowest water uptake credited to a combined effect of eco‐friendly treatment and coating which provides strong interfacial bonding as the treatment eliminates the hemicellulose and lignin, and coating makes the fibers more hydrophobic and acts as a protective layer which strongly opposes to the water absorption…”
Section: Resultsmentioning
confidence: 66%
“…It was observed that fiber‐matrix adhesion and stiffness were enhanced by treatment owing to better mechanical anchoring and wetting. Mukhtar et al remarked an improvement in thermal stability, crystallinity, and tensile strength after sodium bicarbonate treatment of sugar palm fibers credited to an increase in the content of cellulose. An improvement in mechanical and thermal properties of hemp/polyester composites was found by sodium bicarbonate treatment .…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of the natural fibre comes with a lot of benefits which include but not limited to low density, low cost, availability, renewability, biodegradability, and nonabrasive [6][7][8][9][10][11]. Therefore, combining these two different reinforcing materials, a hybrid composite with balance performance especially cost performance and lightweight can be synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…Also, natural fibres offer many advantages over synthetic fibres, such as being readily available at low cost, having low density, being non-toxic and non-abrasive, and having acceptable specific properties (Jawaid et al 2013;Isma'ila et al 2016;Rashid et al 2017c). However, they have certain drawbacks, including poor fibre-matrix interfacial bonding, high moisture absorption, and low thermal stability.…”
Section: Introductionmentioning
confidence: 99%